Identification of short circuits in electronic boards using electrical impedance spectroscopy - Yves Santos Borges; Pedro Bertemes Filho (Revista Principia)
The increasing dependence on electronics in both industrial and public sectors highlights the critical importance of high-quality printed circuit boards (PCBs) to ensure reliability and user confidence. Traditional fault detection methods include visual inspections, automated optical inspection (AOI), in-circuit testing (ICT), and functional testing. However, these methods may not effectively detect subtle faults, such as early-stage corrosion or tiny unintended conductive paths, which would later lead to failures. Electrical Impedance Spectroscopy (EIS) emerges as a powerful tool in this context due to its non-destructive nature and ability to provide detailed insights into the electrical properties of materials and structures within a PCB. This study aims to investigate the types of faults in printed circuits using Electrical Impedance Spectroscopy (EIS). A printed circuit board was developed using phenolic material with varying track thicknesses to simulate short circuits and different levels of corrosion. Measurements of the electrical impedance spectrum between the track and the ground plane were conducted over 1 kHz to 500 kHz. The distances between tracks were measured using high-resolution microscope images. The key finding from this study is that the phase of the electrical impedance increases with the severity of the short circuit, particularly in thinner tracks. This demonstrates the potential of EIS to detect and quantify faults that other methods may misidentify, offering a quantitative approach to assessing and potentially predicting PCB failures before they lead to device malfunctions.